2018
DOI: 10.1016/j.compchemeng.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

High-order approximation of chromatographic models using a nodal discontinuous Galerkin approach

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Example 4.3. In this example, we compare our simulation with the test given in [14], section 4.22. The parameters are chosen from Table 5 with N t = 5000.…”
Section: Different Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Example 4.3. In this example, we compare our simulation with the test given in [14], section 4.22. The parameters are chosen from Table 5 with N t = 5000.…”
Section: Different Methodsmentioning
confidence: 99%
“…The authors validate their scheme against other flux-limiting schemes available in the literature. To see about discontinuous Galerkin approximation for system (2.1) we refer to [11,14,15]. Recently in [19] a transport model is used to describe gradient elution in liquid chromatography.…”
Section: Preliminaries and Problem Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the Gibbs phenomenon is of less concern and arbitrary high-order methods can be used for cost-efficient simulations. Therefore, we (Meyer et al (2018)) suggested to use a hp-type DG method, proposed by Warburton (2002, 2008), to cost-efficiently predict realistic chromatographic systems. In short, the computational domain is partitioned into non-overlapping elements while the solution within an element is approximated by an pth order polynomial.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…ChromaTech is based on a discontinuous Galerkin spectral element method in nodal form (Hesthaven andWarburton, 2002, 2008), that allows arbitrary high-order (spectral) convergence within elements while retaining stability of the method (Meyer et al, 2018b(Meyer et al, , 2019. Moreover, the method is massconservative and can be naturally extended to support mesh refinement with adaptive element sizes and polynomial orders (hp-adaptivity), see e.g.…”
Section: Introductionmentioning
confidence: 99%